Settlement Calculations of Large-diameter Bored Piles Socketed in Weak Rocks in the Area of a Double Track Railway Project (Chira Junction to Khon Kaen Station) - Mahakhotchasenichai, Ketkaewngoen; Sakunphanich, Neti; Boonyarak, Thayanan (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 27, 2022)
At the present, many public utilities transportation of Thailand have been developed in accordance with the government’s policy that manages to connect urban and rural areas, for example, SRT Double Track Railway – Nakhon Ratchasima (Chira Junction) to Khon Kaen, Bang Pa-In – Nakhon Ratchasima Intercity Motorway Project (M6), etc. The runway structures of those projects are usually placed on large-diameter bored piles which run along the outskirts. Those areas have rarely been under engineering construction. Therefore, the engineering data is very limited. In this article, the calculations of settlement values of large-diameter bored piles socketed in weak rocks in the area of SRT Double Track Railway – Nakhon Ratchasima (Chira Junction) to Khon Kaen) are explained by traditional methods, a computer program method and comparisons with the data obtained from static load tests. The comparative results show that experimental pile shortening values are approximately 0.55-1.35 times of those of methods.